2021
DOI: 10.1063/5.0046174
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation from arbitrary nanoporous membrane configurations: An effective evaporation coefficient approach

Abstract: Thin-film evaporation from nanoporous membranes is a promising cooling technology employed for the thermal management of modern electronic devices. We propose an effective one-dimensional analytical approach that can accurately predict the temperature and density jump relations, and evaporation rates, for arbitrary nanoporous membrane configurations. This is accomplished through the specification of an effective evaporation coefficient that encompasses the influence of different system parameters, such as poro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Under such conditions, the boundary slip effects (Karniadakis et al 2005a) or the inner friction force between molecules may add to the two-dimensional feature. John et al (2021) reported the existence of Moffatt eddies near the top pore wall at a lower porosity (0.25) and Kn (0.05). They concluded that the one-dimensionality of vapour flow tends to break down with small porosity and low Kn.…”
Section: 9mentioning
confidence: 99%
See 4 more Smart Citations
“…Under such conditions, the boundary slip effects (Karniadakis et al 2005a) or the inner friction force between molecules may add to the two-dimensional feature. John et al (2021) reported the existence of Moffatt eddies near the top pore wall at a lower porosity (0.25) and Kn (0.05). They concluded that the one-dimensionality of vapour flow tends to break down with small porosity and low Kn.…”
Section: 9mentioning
confidence: 99%
“…Boundary 4 is simply a specular surface which does not affect the evaporation process. The boundary 5 is set in such a way that vapour near 5 has a macroscopic speed u ∞ (John et al 2021;Wu et al 2001). Since the evaporation problem has only one independent variable, we control the evaporation rate through u ∞ and the results of ρ ∞ and T ∞ will be outputs of the DSMC simulation.…”
Section: Simulation Set-upmentioning
confidence: 99%
See 3 more Smart Citations